Plan de marketing internacional para mejorar la gestión de ventas de la empresa "Coctiki Cocteles" - Yapud, Brayan P. (2019)
The present investigation deals with the elaboration of a marketing plan for the company "Coctiki Cocktails", for this a general objective has been proposed that is to design an international marketing plan to improve the sales management of the company Coctiki Cocktails. The marketing is oriented towards the attitude of customers, the product, innovation and advertising, based on the requirements of customers to determine the supply of goods and services. The scientific theoretical bases were approached, where the variables of study as international marketing and sales management were conceptualized. International marketing is one of the ways to publicize the product in the global market due to the saturation of the national market or the low valuation of local products, in such a reason, it is necessary to face new competitors at the world level, through The international marketing plan the company will focus on looking for markets where the product is hosted and have the opportunity to grow and take advantage of production capacity. The study was based on the qualitative - quantitative paradigm, because the characteristics of the company, customers and especially the product were analyzed. The methods used were inductive - deductive, and analytical - synthetic. The study population was made up of the owner manager, workers and customers of the company. As a result, the problem was identified that the company lacks an international marketing plan so that sales have decreased, as well as not having an established strategy, the company is losing its presence in the local market. As for the preferences of cocktails in the international market, there is an opportunity to export to the Chilean market. As a proposal, an international marketing plan was proposed that covers the analysis of the company, corporate image, objectives, market research, product, price, place, communication and sales projection.